Development and operation of a novel non-invasive opto-acoustic underwater fish observatory in Kiel Bight, Southwestern Baltic Sea - Joachim P. Gröger; Boris Cisewski; Sabah Badri-Hoeher; Gordon Böer; Karin Boos; Catriona Clemmesen; Ala Cojocaru; Verena Dauben; Peter A. Hoeher; Andreas Lehmann; Sebastian Matz; Hela Mehrtens; et al. (Frontiers in Marine Science, 2024)
This study presents a trilateral test array of new opto-acoustic Underwater Fish Observatories (UFOs) that were operated and tested in Kiel Bight as part of the “UFOTriNet” project. While hydroacoustic and optical techniques have so far been used individually to observe and monitor fish stocks, we present a coupled hybrid system consisting of an optical device intended to scan the near-field as a subsample of a spatially larger medium-to-far-field, scanned by an acoustical device. The optical device consists of two residual light amplifying camera modules able to detect and classify various marine species at a high resolution in the range of at max 4 meters in the study area. To compensate for this spatial limitation, the acoustical component consists of a 2D imaging sonar with a maximum range of 50 m, albeit with a lower resolution. Species affiliation, morphometric characteristics of fish and other marine organisms were stereo-optically detected and classified in the nearfield, blended with acoustical activity in medium to far range, and projected onto the entire insonified area using a hybrid algorithm. Through the synchronous acquisition of multiparametric abiotic and biotic data, UFO allows an automatic, continuous, and non-invasive long-term monitoring of various fish and other marine species and their habitats at regional hotspots. An 86-day multiparametric sample revealing an abrupt shift from a clupeid fish to a gelatinous plankton dominated regime in summer/autumn 2021 in Kiel Fjord is used to demonstrate the potential of UFO for various applications.

Vertical Migration of Pelagic and Mesopelagic Scatterers From ADCP Backscatter Data in the Southern Norwegian Sea - Boris Cisewski; Hjálmar Hátún; Inga Kristiansen; Bogi Hansen; Karin Margretha H. Larsen; Sólvá Káradóttir Eliasen; Jan Arge Jacobsen (Frontiers in Marine Science, 2021)
Records of backscatter and vertical velocity obtained from moored Acoustic Doppler Current Profilers (ADCP) enabled new insights into the dynamics of deep scattering layers (DSLs) and diel vertical migration (DVM) of mesopelagic biomass between these deep layers and the near-surface photic zone in the southern Norwegian Sea. The DSL exhibits characteristic vertical movement on inter-monthly time scales, which is associated with undulations of the main pycnocline between the warm Atlantic water and the underlying colder water masses. Timing of the DVM is closely linked to the day-night light cycle—decent from the photic zone just before sunrise and ascent immediately after sunset. Seasonal variations are also evident, with the highest DVM activity and lowest depth averaged mean volume backscatter strength (MVBS) during spring. This suggests that both oceanographic and optical conditions are driving the complex dynamics of pelagic and mesopelagic activity in this region. We hypothesize that the increased abundance of calanoid copepods in the near-surface layer during spring increases the motivation for vertical migration of pelagic and mesopelagic species, which therefore can explain the increased DVM activity during this season.

Operating Cabled Underwater Observatories in Rough Shelf-Sea Environments: A Technological Challenge - Philipp Fischer; Holger Brix; Burkard Baschek; Alexandra Kraberg; Markus Brand; Boris Cisewski; Rolf Riethmüller; Gisbert Breitbach; Klas Ove Möller; Jean-Pierre Gattuso; Samir Alliouane; Willem H. van de Poll; et al. (Frontiers in Marine Science, 2020)

The ICES Working Group on Oceanic Hydrography: A Bridge From In-situ Sampling to the Remote Autonomous Observation Era - César González-Pola; Paula Fratantoni; Karin M. H. Larsen; N. Penny Holliday; Stephen Dye; Kjell Arne Mork; Agnieszka Beszczynska-Möller; Hedinn Valdimarsson; Alexander Trofimov; Hjalte Parner; Holger Klein; Boris Cisewski; et al. (Frontiers in Marine Science, 2019)

Modification by lateral mixing of the Warm Deep Water entering the Weddell Sea in the Maud Rise region - Harry Leach; Volker Strass; Boris Cisewski (Ocean Dynamics, 2011)

Physiology, growth, and development of larval krill Euphausia superba in autumn and winter in the Lazarev Sea, Antarctica - Bettina Meyer; Veronica Fuentes; Citlali Guerra; Katrin Schmidt; Angus Atkinson; Susanne Spahic; Boris Cisewski; Ulrich Freier; Alejandro Olariaga; Ulrich Bathmanna (Limnology and Oceanography, 2009)
The physiological condition of larval Antarctic krill was investigated during austral autumn 2004 and winter 2006 in the Lazarev Sea. The condition of larvae was quantified in both seasons by determining their body length (BL), dry weight (DW), elemental and biochemical composition, stomach content analysis, and rates of metabolism and growth. Overall the larvae in autumn were in better condition under the ice than in open water, and for those under the ice, condition decreased from autumn to winter. Thus, growth rates of furcilia larvae in open water in autumn were similar to winter values under the ice (mean, 0.008 mm d −1 ), whereas autumn underice values were higher (0.015 mm d −1 ). Equivalent larval stages in winter had up to 30% shorter BL and 70% lower DW than in autumn. Mean respiration rates of winter larvae were 43% lower than of autumn larvae. However, their ammonium excretion rates doubled in winter from 0.03 to 0.06 µg NH 4 DW −1 h −1 , resulting in mean O:N ratios of 46 in autumn and 15 in winter. Thus, differing metabolic substrates were used between autumn and winter, which supports a degree of flexibility for overwintering of larval krill. The larvae were eating small copepods ( Oithona spp.) and protozoans, as well as autotrophic food under the ice. The interplay between under‐ice topography, apparent current speed under sea ice, and the swimming ability of larval krill is probably critical to whether larval krill can maintain position and exploit suitable feeding areas under the ice.